2012
DOI: 10.2139/ssrn.2166863
|View full text |Cite
|
Sign up to set email alerts
|

Urban Poverty in Bangladesh: Causes, Consequences and Coping Strategies

Abstract: BWPI Working Paper 178Creating and sharing knowledge to help end poverty www.manchester.ac.uk/ overty in Bangladesh: causes, strategies 8Creating and sharing knowledge to help end poverty www.manchester.ac.uk/bwpi 2 AbstractBustees are places where physical, social, economic and political vulnerabilities collide, creating a multi-layered blanket of vulnerability for their residents. Although income is central to day-to-day survival in an urban environment in which cash income is needed to meet a household's ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
34
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(35 citation statements)
references
References 80 publications
(154 reference statements)
1
34
0
Order By: Relevance
“…Across the four communities, rental tenants constituted between 66 and 83 per cent of all households (Banks 2012). Rent and utility costs -costing on average between 18 to 22 per cent of the monthly incomes of tenants across the four settlementscombined with expenditures on food, fuel and health care, lead to high monthly expenditures that few low-income urban households can be assured of meeting with their unstable incomes.…”
Section: Urban Livelihoods Strategies and Their Limitationsmentioning
confidence: 99%
See 4 more Smart Citations
“…Across the four communities, rental tenants constituted between 66 and 83 per cent of all households (Banks 2012). Rent and utility costs -costing on average between 18 to 22 per cent of the monthly incomes of tenants across the four settlementscombined with expenditures on food, fuel and health care, lead to high monthly expenditures that few low-income urban households can be assured of meeting with their unstable incomes.…”
Section: Urban Livelihoods Strategies and Their Limitationsmentioning
confidence: 99%
“…Rent and utility costs -costing on average between 18 to 22 per cent of the monthly incomes of tenants across the four settlementscombined with expenditures on food, fuel and health care, lead to high monthly expenditures that few low-income urban households can be assured of meeting with their unstable incomes. Only 45 per cent of households break-even or have an income surplus each month once these costs have been taken into account (Banks 2012), 4 and if taking into account the average monthly expenditure on health costs on top of this, only one in three households have sufficient income to cover household expenditures without going into debt. The research found three strategies distinguishing between coping and improving households regardless of their employment status: labour mobilization; investment in productive assets; and the pursuit of alternative forms of financing through savings and loans.…”
Section: Urban Livelihoods Strategies and Their Limitationsmentioning
confidence: 99%
See 3 more Smart Citations